CARTOGRAPHIC SUPPORT OF CORRELATION EXTREME NAVIGATION SYSTEMS - Babeniuk, Ganna (Proceedings of National Aviation University (archive), 2020)
In this paper correlation extreme navigation system and its improvement is presented. Extreme navigation system is based on maps analysis, therefore accuracy of maps is very important. Magnetic field maps as the main source of information can include deviations of measurements due to variations of magnetic field. In order to minimize the influence of variations of magnetic field on magnetic field measurements magnetic observatories are used. During the process of magnetic field maps creation with a help of variation station from time to time variation station sends the request to magnetic observatory for reference data in order to correct the deviations of local magnetometers that appears due to variations of magnetic field. The problem of the given approach is that variation stations usually are located in remote areas and usage of standard Internet protocol for reference data request from observatory in some cases is impossible. The given article represents new approach for data retrieving from magnetic observatory based on usage of satellite communication.